2020
DOI: 10.1007/jhep02(2020)091
|View full text |Cite
|
Sign up to set email alerts
|

An inverse mass expansion for the mutual information in free scalar QFT at finite temperature

Abstract: We study the entanglement entropy and the mutual information in coupled harmonic systems at finite temperature. Interestingly, we find that the mutual information does not vanish at infinite temperature, but it rather reaches a specific finite value, which can be attributed to classical correlations solely. We further obtain high and low temperature expansions for both quantities. Then, we extend the analysis performed in the seminal paper by Srednicki [1] for free real scalar field theories in Minkowski space… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
5
0
1
Order By: Relevance
“…But the homogeneous polynomials are a finite dimensional vector space, meaning that the constants A k,a,d n,m,j 1 ,j 2 can be computed through a straightforward finite dimensional linear system of equations. 14 Here we note that for these coefficients, the indices k and a are indices of the Gegenbauer polynomials, the index d corresponds to the spatial dimension, while n, m, j 1 , j 2 label a basis for homogeneous polynomials. There is likely no neat formula for these coefficients in general.…”
Section: Jhep04(2024)019mentioning
confidence: 99%
See 1 more Smart Citation
“…But the homogeneous polynomials are a finite dimensional vector space, meaning that the constants A k,a,d n,m,j 1 ,j 2 can be computed through a straightforward finite dimensional linear system of equations. 14 Here we note that for these coefficients, the indices k and a are indices of the Gegenbauer polynomials, the index d corresponds to the spatial dimension, while n, m, j 1 , j 2 label a basis for homogeneous polynomials. There is likely no neat formula for these coefficients in general.…”
Section: Jhep04(2024)019mentioning
confidence: 99%
“…For instance, Srednicki had to impose an ultraviolet cutoff by discretizing the sphere with a finite lattice. Rather than deal with this divergence directly, some authors choose to study a related quantity, the mutual information of two spatially JHEP04(2024)019 separated regions [12][13][14][15]. Given a bipartite state with density operator ρAB and reduced density operator ρA and ρB , the mutual information can be defined in terms of entropy, I = S(ρ A ) + S(ρ B ) − S(ρ AB ).…”
Section: Introductionmentioning
confidence: 99%
“…In [1] we generalize the approach of [42] in a method for the perturbative calculation of the spectrum of the reduced density matrix and entanglement entropy as well. In [6,7] we study free massive scalar QFT at finite temperature. We show that it is the mutual information that obeys an area law and that there is a natural way to separate the contribution of classical and quantum correlations to the mutual information.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that in lattice spin systems the mutual information obeys an area law bound [240]. This Part of the dissertation is based on the publications [1,6,7]. Its structure is as follows: in section 8, we review the derivation of entanglement entropy in systems of coupled harmonic oscillators lying at their ground state and extend the calculation in free scalar field theory including a mass term, closely following [42].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation